Shakedown of elastic-thermo-plastic structures - Vranković, Nikola; Stegić, Milenko; Kranjčević, Nenad (Computer Assisted Methods in Engineering and Science, 2000)
Recently formulated shakedown theorems for materials with temperature-dependent yield stress [1] are applied to evaluation of the elastic shakedown boundary. In order to simulate actual shakedown behaviour of elastic-thermo-plastic structures resulting from experimental investigations, the material model of the German mild steel St 37 is considered. It is found that the obtained elastic shakedown boundaries are within the corresponding boundaries based on the classical shakedown theory. Two examples are compared with the well-known solutions obtained for the neglected yield stress dependence on temperature.